Biochar Technology as a Go Green Movement in Indonesia - Gustan Pari (Journal of Wetlands Environmental Management, 2014)
Charcoal has long been known by the community in its use either as energy sources or for agriculture/forestry-related aspects.  Beginning from the discovery of the so-called Terra Preta, the role of charcoal in improving soil fertility and enhancing its productivity at agriculture as well as forestry lands has attracted remarkable attention internationally ever since.  Raw material for charcoal can be wood or other ligno-cellulosic stuffs (e.g. coconut shells, oil-palm shells, rice husks, wood sawdust, nut shells, etc).  Technology in charcoal manufacture commonly employed by the community comprises heaping-kiln, drum kiln, and dome-shaped kiln systems.  Such manufacture technology is simply carbonizing the ligno-cellulosic stuffs inside the kiln into charcoal.  The charcoal yield usually ranges about 20-25% (w/w), implying that as much 75-80% of the stuffs is lost as smoke that further escape to the air.  Environment concerns arise since such escaped smoke can pollute the atmosphere and hence contribute to the global warming.  Measures are urgently needed to reduce the amount of such escapes among others, as developed by the Center for Research and Development on Forestry Engineering and Forest Products Processing (CRDFEFPP, Indonesia) by cooling the smoke, during the carbonization of ligno-cellulosic stuffs, thereby condensing it into liquid smoke (popularly called as wood vinegar). Through intensive and tedious researches, it is found out that the wood vinegar (as charcoal by-product) could effectively function as bio-pesticides and bio-fertilizers.  Meanwhile, application of charcoal to the seedlings of forestry plant species reveals positive responses as shown by the increase in biomass weight of those plants on other positive plant-growth aspects (e.g. stem height and diameter).  Likewise, the use of charcoal combined with compost (i.e. organic fertilizer that results from bio-conversion of biomass stuffs) could enhance as much 2-3 times the production of vegetables plants as the control (untreated plants).  This in all strongly indicates the charcoal and wood-vinegar manufacture entirely called as essentially the bio-char technology, can convert biomass stuffs (previously regarded as not or less useful) into value-added or more useful products (charcoal and wood vinegar).